PENGARUH MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE DENGAN BANTUAN MEDIA GAMBAR 3D TERHADAP HASIL BELAJAR MENULIS DESKRIPSI SISWA KELAS IV SDN 2 SOBO - Dharma Saputra, Dwi; Aan Nurfahrudianto; Sutrisno Sahari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on the results of observations and experiences of researchers that Indonesian language learning in descriptive writing skills still uses the lecture method centered on the teacher, resulting in a passive and less interesting learning atmosphere, this has an impact on students' ability to write descriptions which tend to be low and less than optimal. This study uses a quantitative approach and uses a quasi-experimental research technique (Quasi Experimental Design) with a Nonequivalent Control Group Design design. The subjects of this study were grade IV students of SDN 2 Sobo. This study uses inferential statistical analysis research techniques using the SPSS program version 28.0. The inferential statistics used are t-tests, Normality tests and homogeneity tests are carried out as prerequisites before conducting t-tests. The conclusions of this study are (1). The results of learning to write descriptions using the lecture method with the help of image media, the learning results of grade IV students of SDN 2 Sobo <70. (2). The results of learning to write descriptions after using the Example No Example learning model with the help of 3D image media, the learning results of grade IV students of SDN 2 Sobo ≥ 70. (3). The application of the Example Non Example learning model with the help of 3D image media has an effect on the learning outcomes of grade IV students of SDN 2 Sobo in the material of writing descriptions. This is based on the results of data analysis with the t-test that the Asymp.sig. (2-failed) value obtained a result of .000. where the Asymp. Sig. (2failed) value is .000 <0.05. then the effect is said to be significant. Based on the results of the conclusions of this study, it is expected that educators can apply learning models and learning media in order to attract students' interest in learning activities, and help students to better understand the material.